cnAnalysis450k: an R package for comparative analysis of 450k/EPIC Illumina methylation array derived copy number data - Knoll, Maximilian; Debus, Jürgen; Abdollahi, Amir (Bioinformatics, 2017)
AbstractMotivation. Detailed copy number (CN) variation data can be obtained from 450k or EPIC Illumina methylation assays. However, the effects of different p
Gesehen am 25.09.2018